SLMToolBox: enterprise service process modelling and simulation by coupling DEVS and services workflow. (2016) - Bazoun, Hassan; Ribault, Judicael; Zacharewicz, Gregory; Ducq, Yves; Boyé, Hadrien
Market competition is pushing companies to differentiate themselves from competitors by developing customised services in addition to their original production (either physical or digital). It drives the emergence of service process modelling to describe precisely the composition of services. To this end, this paper presents the key concept of the transformation of EA* and BPMN models into simulation workflows. Then, it introduces the implementation done with the SLMToolBox that is a service graphical modeller, model transformer, and simulation engine. In addition, enterprises are facing situations where future (undeveloped yet) enterprise services need to be integrated with existing ones. To go further and for a better integration and deployment of service models in the enterprise, we propose to combine service process M&S with service calls execution workflow. To achieve that goal, we are mashing up simulation of services modelled with existing enterprise web services calls.